FILOSOFI DAN PENDIDIKAN KARAKTER DALAM TEKS SíŠRAT Mí‰NAK SARí‰HAS DUMUGI Mí‰NAK SORANGAN MELALUI TOKOH AMIR AMBYAH - Hayuningtyas, Amita; Ekowati, Venny Indria (Diksi, 2020)
(Title: Philosophy and Character Education in the Text of "Síªrat Ménak Saréhas Dumugi Ménak Sorangan" through Amir Ambyah's Character). This research is a philological study in the text of Síªrat Ménak Saréhas dumugi Ménak  Sorangan. Philosophical studies are in the form of an inventory, description, transliteration, edits and translations of the text of Saréhas dumugi Ménak Sorangan. This study aims to describe character education in the text of Sérat Ménak Saréhas dumugi Ménak Sorangan by using descriptive research methods. The object of the research is the text of Sérat Ménak Saréhas dumugi Ménak Sorangan. The way how to collect data in this research is by using a data card which is further described. There are 5 results of this study. First, the description of the text of Sérat Ménak Saréhas dumugi Ménak Sorangan is still intact andthe letters are still clear. Second, by using standard transliteration, the text of Síªrat Ménak Saréhas dumugi Ménak Sorangan which reads Javanese script is changed to Latin script. Third, using standard edition text edits, there are 5 words that get edits, then all changes in edited text are explained in the critics apparatus. Fourth, the results of text translation using bahasa Indonesia and the free translation method are related to the context. Fifth, the contents of the text of Sérat Ménak Saréhas dumugi Ménak Sorangan describe 9 pillars of character education, namely: (1) obedience to God, (2) responsibility, (3) wise, (4) respect and courtesy, (5) generous, love to help , (6) courageous, (7) kind and humble,(8) tolerance, peace and unity, and (9) leadership. The character education is related to the meaning of the illumination symbol wadí¥ní¥ gapurí¥ ríªnggan in the text of Sérat Ménak Saréhas dumugi Ménak Sorangan.Keywords: Philological study, character education, illumination of wíªdí¥ní¥ gapurí¥ ríªnggan, Síªrat Ménak Saréhas dumugi Ménak Sorangan